2023
DOI: 10.30880/jtet.2023.15.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychological Well-Being onStudents’ Perception ofOnline Learning During the COVID-19Pandemic

Abstract: The outbreak of COVID-19 has led to a global lockdown, and universities have shifted to online learning. Despite the various efforts made by universities for students' online learning during the pandemic, not much has been identified about how students perceived online learning and how it affected their psychological well-being (PWB). This study examines the differences between male and female students' perceptions of online learning during the pandemic. A quantitative research design was used to measure the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition to physical activity, people's psychological status changed a lot during the period of online education and curfew. Rozali et al [49], in their survey of 127 technical students in Malaysia, investigated the impact of the pandemic on health, looking at gender differences. A study with a quantitative research plan showed that there was no significant difference in psychological well-being related to gender.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to physical activity, people's psychological status changed a lot during the period of online education and curfew. Rozali et al [49], in their survey of 127 technical students in Malaysia, investigated the impact of the pandemic on health, looking at gender differences. A study with a quantitative research plan showed that there was no significant difference in psychological well-being related to gender.…”
Section: Literature Reviewmentioning
confidence: 99%